Non-viral generation of marmoset monkey iPS cells by a six-factor-in-one-vector approach. - Katharina Debowski; Rita Warthemann; Jana Lentes; Gabriela Salinas-Riester; Ralf Dressel; Daniel Langenstroth; Jörg Gromoll; Erika Sasaki; Rüdiger Behr (PLoS ONE, 2015)
Groundbreaking studies showed that differentiated somatic cells of mouse and human origin could be reverted to a stable pluripotent state by the ectopic expression of only four proteins. The resulting pluripotent cells, called induced pluripotent stem (iPS) cells, could be an alternative to embryonic stem cells, which are under continuous ethical debate. Hence, iPS cell-derived functional cells such as neurons may become the key for an effective treatment of currently incurable degenerative diseases. However, besides the requirement of efficacy testing of the therapy also its long-term safety needs to be carefully evaluated in settings mirroring the clinical situation in an optimal way. In this context, we chose the long-lived common marmoset monkey (Callithrix jacchus) as a non-human primate species to generate iPS cells. The marmoset monkey is frequently used in biomedical research and is gaining more and more preclinical relevance due to the increasing number of disease models. Here, we describe, to our knowledge, the first-time generation of marmoset monkey iPS cells from postnatal skin fibroblasts by non-viral means. We used the transposon-based, fully reversible piggyback system. We cloned the marmoset monkey reprogramming factors and established robust and reproducible reprogramming protocols with a six-factor-in-one-construct approach. We generated six individual iPS cell lines and characterized them in comparison with marmoset monkey embryonic stem cells. The generated iPS cells are morphologically indistinguishable from marmoset ES cells. The iPS cells are fully reprogrammed as demonstrated by differentiation assays, pluripotency marker expression and transcriptome analysis. They are stable for numerous passages (more than 80) and exhibit euploidy. In summary, we have established efficient non-viral reprogramming protocols for the derivation of stable marmoset monkey iPS cells, which can be used to develop and test cell replacement therapies in preclinical settings.